Modelling amoebic brain infection caused by Balamuthia mandrillaris using a human cerebral organoid. - Nongnat Tongkrajang; Porntida Kobpornchai; Pratima Dubey; Urai Chaisri; Kasem Kulkeaw (Public Library of Science (PLoS), 2024)
The lack of disease models adequately resembling human tissue has hindered our understanding of amoebic brain infection. Three-dimensional structured organoids provide a microenvironment similar to human tissue. This study demonstrates the use of cerebral organoids to model a rare brain infection caused by the highly lethal amoeba Balamuthia mandrillaris. Cerebral organoids were generated from human pluripotent stem cells and infected with clinically isolated B. mandrillaris trophozoites. Histological examination showed amoebic invasion and neuron damage following coculture with the trophozoites. The transcript profile suggested an alteration in neuron growth and a proinflammatory response. The release of intracellular proteins specific to neuronal bodies and astrocytes was detected at higher levels postinfection. The amoebicidal effect of the repurposed drug nitroxoline was examined using the human cerebral organoids. Overall, the use of human cerebral organoids was important for understanding the mechanism of amoeba pathogenicity, identify biomarkers for brain injury, and in the testing of a potential amoebicidal drug in a context similar to the human brain.